Economic evaluation of nile tilapia juvenile production, feed with commercial ration and with primary production come from organic and inorganic fertilization - Leonardo, Antônio Fernando Gervásio [UNESP]; Tachibana, Leonardo [UNESP]; Corrêa, Camila Fernandes; Baccarin, Ana Eliza [UNESP]; Filho, João Donato Scorvo [UNESP] (My University, 2009)
Study objective was to evaluate economically a Nile tilapia juvenile production, employing different feeding techniques. Tilapia fingerlings of 8g were stocked at 5 fish m-2 stocking in 50 and 150 m2 ponds, during 75 days. Treatments were: inorganic fertilization (P205 and N); organic fertilization (poultry manure) and commercial ration (32% CP). Water quality results were considered adequate for fish rearing. In juvenile production there were significant differences among treatments for individual final weight, medians were: for inorganic fertilization 12.92g (13.35g in 50 m2 and 12.49g in 150 m2); for organic fertilization 30.55g (33.69g in 50 m2 and 27.40g in 150 m2) and for commercial ration 51.23g (52.90g in 50 m2 and 50.15g in 150 m2). Survival rate ranged from 63 to 71%, with no statistic difference. Commercial ration was effective to bigger juvenile production, with a better market value. Costs considered in economic analyses were tilapia fingerlings, fertilizer, ration, labor and installation depreciation. Obtained information showed that juvenile production in 50 m2 ponds is not viable economically and, in 150 m2, production is viable only when commercial ration is used.
Keywords: Oreochromis niloticus; Ponds; Vale do ribeira